2015
DOI: 10.1136/gutjnl-2014-308835
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy study of anorectal manometry for diagnosis of dyssynergic defecation

Abstract: Objective The diagnostic accuracy of anorectal manometry (AM), which is necessary to diagnose functional defaecatory disorders (FDD), is unknown. Using blinded analysis and standardised reporting of diagnostic accuracy (STARD), we evaluated whether AM could discriminate between asymptomatic controls and patients with functional constipation (FC). Design Derived line-plots of anorectal pressure profiles during simulated defaecation were independently analysed in random order by 3 expert observers blinded to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
164
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(200 citation statements)
references
References 54 publications
8
164
2
8
Order By: Relevance
“…37 Only type IV dyssynergia had a positive likelihood ratio of 2.3, indicative of a "small" increase in the likelihood of disease. 37 …”
Section: Types Of Pelvic Floor Dyssynergiamentioning
confidence: 99%
See 2 more Smart Citations
“…37 Only type IV dyssynergia had a positive likelihood ratio of 2.3, indicative of a "small" increase in the likelihood of disease. 37 …”
Section: Types Of Pelvic Floor Dyssynergiamentioning
confidence: 99%
“…26 There is substantial agreement among expert observers for the overall diagnosis dyssynergia (kappa = 0.35). 37 However, dyssynergia is not useful for discriminating between healthy people and patients because 90% of healthy volunteers and patients with functional constipation had an abnormal anorectal pressure profile during simulated defecation. 37 Only type IV dyssynergia had a positive likelihood ratio of 2.3, indicative of a "small" increase in the likelihood of disease.…”
Section: Types Of Pelvic Floor Dyssynergiamentioning
confidence: 99%
See 1 more Smart Citation
“…70 Regarding the functional defecation disorders, in the previous classification only patients with functional constipation would be eligible to be diagnosed with a defecatory disorder. However, because it has been recognized that patients with IBS and pelvic floor dysfunction can have an association with dyssynergic dysfunction, 71 and they can be treated with biofeedback irrespective of their association with IBS, 72 IBS-C have now been included in the Rome IV definition. 70 In addition, criteria for inadequate propulsive forces and inappropriate contraction of the anal sphincter and/or pelvic floor muscles are no longer specified because they vary among different techniques.…”
Section: Anorectal Disordersmentioning
confidence: 99%
“…Previous studies have reported the presence of dyssynergic defecation in 27-59% patients with CIC [14], a condition best assessed using anorectal manometry. Although anorectal manometry may be helpful in defining the causes of constipation in future studies, the technique is not only technically cumbersome and expensive for a large cohort study; there also is lack of consensus on its applicability to constipation management [16]. Although the understanding of defecatory disorders is increasing due to the availability of diagnostic tests, including 3D-transit system imaging and manometry, and magnetic resonance imaging (MRI), on a practical basis, defecatory diaries are the most feasible method for large-study enrollment despite evidence of discordance between patient-reported symptom diaries of constipation and objective measures [17].…”
mentioning
confidence: 99%